Abruptio placenta: an obstetrician's nightmare - Abhirami GR; Sathyavani C; Maria Cecilia Alexander; Shiny Varghese; Ravi N Patil; Rajnish Samal; Nalini Arun Kumar (Barpeta Obstetrics and Gynaecological Society, 2023)
Background: Abruptio placenta is as an important cause of antepartum hemorrhage (APH) and accounts for 20 - 25% of all cases of APH. It is defined as premature separation of a normally situated placenta before the delivery of the fetus. Abruptio placenta is a serious obstetric condition that increases maternal and neonatal morbidity and mortality. Objectives: This study was undertaken to determine the incidence, etiology, risk factors, clinical presentation and feto-maternal outcome of abruptio placenta. Method: This was a prospective observational study done in Bangalore Baptist Hospital from 2017-2020. The primary outcomes were included the occurrence and frequency of various maternal complications and evaluation of fetal and neonatal outcomes in patients with abruptio placenta. All the pregnant women fulfilling the inclusion criteria were considered for the study. Results: We had a total of 37 women with abruptio placenta during this period with an incidence of 0.4%. The incidence was higher in the age group above 30 years (40.5%) and among primiparous women (54.1%). Pre-eclampsia was identified as the most common risk factor among these women (59.5%). There were 13 women (35.1%) who had an intra-uterine fetal demise at the time of admission. The main mode of delivery among live births was caesarean section (61.5%) and that for intra-uterine fetal demise was vaginal delivery (83.3%). The maternal complications included requirement of blood transfusion (67.6%), disseminated intravascular coagulation (DIC) (3%), hypovolemic shock (11%) and ICU admission (16.2%). There was no maternal mortality among the study population. The perinatal mortality was 48.6 % comprising of 13 intra-uterine fetal demise and 5 early neonatal deaths. Conclusion: Abruptio placenta is associated with poor maternal and fetal outcome. Hence early detection and active management is necessary to reduce maternal and fetal morbidity. Educating the pregnant mother about the importance of antenatal care and easy accessibility to quality antenatal services would go a long way in bringing down the maternal and perinatal morbidity and mortality related with abruptio placenta.